Directional side scattering of light by a single plasmonic trimer. Issue 5 (19th August 2015) - Lu, Guowei; Wang, Yuwei; Chou, R. Yuanying; Shen, Hongming; He, Yingbo; Cheng, Yuqing; Gong, Qihuang
<x xml:space="preserve">Abstract</x> Various gold nanoparticles trimers assembled by AFM nanomanipulation are investigated in situ. Directional side scattering by single plasmonic oligomers is demonstrated with the directivity up to 7.8 dB and a broad spectral response over 400 nm. It is revealed that the interference of multiple plasmonic resonance modes of the trimer due to near‐field plasmon coupling of the nanoparticles results in the unidirectional scattering.